2007
DOI: 10.1111/j.1542-4758.2007.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of 25(OH) vitamin D insufficiency and deficiency in chronic kidney disease stage 5 patients on hemodialysis

Abstract: Little is known about the magnitude of vitamin D deficiency in patients with stage 5 chronic kidney disease (CKD-5) on hemodialysis (HD). In the present study, we examined the prevalence of vitamin D deficiency in patients with CKD-5 undergoing HD, evaluating the relationship between calcidiol levels with other parameters of mineral metabolism, nutrition/inflammation, functional capacity (FC), and sunlight exposure. Serum 25(OH) vitamin D levels were evaluated in 84 stable patients on chronic HD not receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
99
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 33 publications
8
99
3
3
Order By: Relevance
“…This finding suggests the possibility of a significant number of hemodialysis patients with osteomalacia in our study. We found significantly lower levels of 25hD in diabetics females than in non-diabetics and males, which is in agreement with results of other studies (16)(17)(18).…”
Section: Discussionsupporting
confidence: 83%
“…This finding suggests the possibility of a significant number of hemodialysis patients with osteomalacia in our study. We found significantly lower levels of 25hD in diabetics females than in non-diabetics and males, which is in agreement with results of other studies (16)(17)(18).…”
Section: Discussionsupporting
confidence: 83%
“…Elisa Del Valle reported a prevalence of only 22.6% among patients on HD (18) and Guillermo suggested that 50% of patients with end-stage renal disease (ESRD) had low level of 25(OH)D (19).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD on dialysis (CKD-5D) frequently have low 25(OH)D levels, varying from ,10 ng/ml (25 nmol/L) in 65% of patients in one study (2), to levels ,15 ng/ml (37.5 nmol/L) in 14%-23% of patients in other studies (3,4). Patients on dialysis lack normal renal conversion of 25(OH)D to 1,25-dihydroxyvitamin D [1,25(OH) 2 D], and evidence to support the benefits of increasing 25(OH)D levels with calciferol (cholecalciferol or ergocalciferol) is weak.…”
Section: Introductionmentioning
confidence: 99%